Measuring adaptive teaching in classroom discourse: Effects on student learning in elementary science education - Hardy, Ilonca; Meschede, Nicola; Mannel, Susanne (Frontiers in Education, 2022)
Adaptive teaching is considered fundamental to teaching quality and student learning. It describes teachers’ practices of adjusting their instruction to students’ diverse needs and levels of understanding. Adaptive teaching on a micro level has also been labeled as contingent support and has been shown to be effective in one-to-one and small-group settings. In the literature, the interplay of teachers’ diagnostic strategies and instructional prompts aiming at tailored support are emphasized. Our study adds to this research by presenting a reliable measurement approach to adaptive classroom discourse in elementary science which includes a global index and the single indices of diagnostic strategies, instructional support, and student understanding. Applying this coding scheme, we investigate whether N=17 teachers’ adaptive classroom discourse predicts N=341 elementary school students’ conceptual understanding of „floating and sinking“ on two posttests. In multilevel regression analyses, adaptive classroom discourse was shown to be effective for long-term student learning in the final posttest, while no significant effects were found for the intermediate posttest. Further, the single index of diagnostic strategies in classroom discourse contributed to long-term conceptual restructuring. Overall, teachers rarely acted adaptively which points to the relevance of teacher professional development.